Wage returns to university disciplines in Greece: are Greek higher education degrees Trojan horses? - Ilias Livanos; Konstantinos Pouliakas (Institute for the Study of Labor (IZA), 2009)
This paper examines the wage returns to qualifications and academic disciplines in the Greek labour market. Exploring wage responsiveness across various degree subjects in Greece is interesting, as it is characterised by high levels of graduate unemployment, which vary considerably by field of study, and relatively low levels of wage flexibility. Using micro-data from recently available waves (2002-2003) of the Greek Labour Force Survey (LFS), the returns to academic disciplines are estimated by gender and public/private sector. Quantile regressions and cohort interactions are also used to capture the heterogeneity in wage returns across the various disciplines. The results show considerable variation in wage premiums across the fields of study, with lower returns for those that have a marginal role to play in an economy with a rising services/shrinking public sector. Educational reforms that pay closer attention to the future prospects of university disciplines are advocated.
Keywords: J24; J31; J38; 330; Academic disciplines; wage returns; higher education; Greece; Bildungsertrag; Akademische Berufe; Studienfach; Hochschulreform; Griechenland